Healing of an endodontic-periodontal lesion caused by trauma. A Case report - Hind Alquthami; Ahmed Alquthami; Abdulrhman Alghofili; Shatha Sulaiman Alrushoud (Wolters Kluwer Medknow Publications, 2020)
Endodontic-periodontal lesions can originate from infections of the periodontium or tissues of the dental pulp. Dental trauma to the face can affect teeth and cause pulp necrosis, which, in turn, leads to periodontal breakdown, pocket formation, and alveolar bone loss. These types of lesions are categorized as retrograde periodontal lesions of endodontic origin, which is the same condition of the case presented in this report. A 37-year-old healthy male had trauma 6 months ago and reported with a chief complaint of oral pain while biting on his maxillary right canine. Clinical examination revealed Grade II mobility and a deep periodontal pocket. Radiographic examinations showed an advanced bone resorption around the tooth. Pulp necrosis with symptomatic apical periodontitis was diagnosed. Root canal treatment was performed and the case was followed for one year. Thorough history taking and investigation led to successful outcome, with the tooth exhibiting complete soft - and hard-tissue healing.